2021
DOI: 10.1002/ajoc.202100361
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt‐Catalysed, Ligand‐Controlled Regiodivergent Alkene Hydrosilylation

Abstract: Alkene hydrosilylation is amongst the largest industrial homogenous catalysis processes. Cobalt catalysis offers a sustainable alternative to commonly used platinum catalysts to achieve this transformation. Using two bisiminopyridine cobalt(II) catalysts the regiodivergent hydrosilylation of alkenes has been developed. Variation of pre‐catalyst activator and ligand substituents were investigated to enable the controlled, regiodivergent hydrosilylation of both aryl‐ and alkyl‐substituted alkenes with phenylsila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Based on the experiments and literatures, [33,34] a proposed mechanism was showed in Scheme 2. First, the cobalt catalyst precursor reacts with silane and NaBEt 3 H to provide low-valent [Co] + silyl species I; second, the species I then inserted into alkenes to generate cobalt alkyl intermediate II and forms to intermediates III; in the third step, the species III react with the silane to form the hydrosilylation adduct and the cobalt catalyst enter into the next catalytic cycle.…”
Section: F I G U R Ementioning
confidence: 99%
“…Based on the experiments and literatures, [33,34] a proposed mechanism was showed in Scheme 2. First, the cobalt catalyst precursor reacts with silane and NaBEt 3 H to provide low-valent [Co] + silyl species I; second, the species I then inserted into alkenes to generate cobalt alkyl intermediate II and forms to intermediates III; in the third step, the species III react with the silane to form the hydrosilylation adduct and the cobalt catalyst enter into the next catalytic cycle.…”
Section: F I G U R Ementioning
confidence: 99%
“…In relevant reports, cobalt(II) chlorides have good catalytic activity for hydrosilylation of alkenes. 4,[23][24][25][26][27] In 2016, Huang's group realized the hydrosilylation of aliphatic alkenes using cobalt(II) chlorides supported by phosphine-iminopyridine ligands, and obtained the Markovnikov addition product. 4 In 2017, Lu's group used cobalt(II) chlorides supported by chiral [NNN] pincer ligands to realize the highly enantioselective Markovnikov addition reaction of alkenes and silanes.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] In the study of the mechanism of alkene hydrosilylation, it is found that metal hydride really plays a catalytic role in the catalytic cycle although the pre-catalyst is a metal halide or a metal nitrogen-complex. 22,25,26 In an early study of C-F bond activation, our research group used Co(PMe 3 ) 4 as a catalyst and sodium formate as a reducing agent to realize the selective hydrodefluorination of arylfluoride. 31 In a mechanism study, although the cobalt(II) hydride intermediate could not be isolated, the formation of the cobalt(II) hydride intermediate was confirmed by IR and 1 H NMR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…[1] It has been found that cobalt(II) chlorides have good catalytic activity for hydrosilylation of olefins. [2][3][4][5][6] In the study of the mechanism of olefin hydrosilylation, it is found that metal hydrides do play a catalytic role in the catalytic process although the pre-catalyst is metal halides or metal nitrogen complex. [4,5,7] However, due to the difficult synthesis and instability of metal hydrides, there are relatively few reports on the direct use of cobalt hydrides as catalysts for olefin hydrosilylation.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] In the study of the mechanism of olefin hydrosilylation, it is found that metal hydrides do play a catalytic role in the catalytic process although the pre-catalyst is metal halides or metal nitrogen complex. [4,5,7] However, due to the difficult synthesis and instability of metal hydrides, there are relatively few reports on the direct use of cobalt hydrides as catalysts for olefin hydrosilylation. [8] In this paper, two silyl [P, Si]-chelate cobalt hydrides, respectively.…”
Section: Introductionmentioning
confidence: 99%